2006
DOI: 10.1080/14767050600921307
|View full text |Cite
|
Sign up to set email alerts
|

Is severe perineal damage increased in women with prior anal sphincter injury?

Abstract: Prior anal sphincter laceration does not result in an increased rate of recurrence. Operative vaginal delivery particularly with episiotomy is a risk factor for both initial and recurrent laceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 18 publications
7
39
1
3
Order By: Relevance
“…Studies by Edwards et al (2006) and Scheer et al (2009) support the findings in this study, while Lowder (2007) reported that women who had experienced severe perineal trauma with their index pregnancy, were at increased risk of subsequent perineal trauma in comparison to women with no history of perineal trauma (7.2% versus 2.3%). This risk of recurrence was increased as a result of episiotomy, malpresentation, shoulder dystocia, and birth weight greater than 3500 grams [19,20,26]. These associations have also been reported elsewhere [18,20,32].…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Studies by Edwards et al (2006) and Scheer et al (2009) support the findings in this study, while Lowder (2007) reported that women who had experienced severe perineal trauma with their index pregnancy, were at increased risk of subsequent perineal trauma in comparison to women with no history of perineal trauma (7.2% versus 2.3%). This risk of recurrence was increased as a result of episiotomy, malpresentation, shoulder dystocia, and birth weight greater than 3500 grams [19,20,26]. These associations have also been reported elsewhere [18,20,32].…”
Section: Discussionmentioning
confidence: 55%
“…This risk of recurrence was increased as a result of episiotomy, malpresentation, shoulder dystocia, and birth weight greater than 3500 grams [19,20,26]. These associations have also been reported elsewhere [18,20,32]. …”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…A recent population‐based study in Australia found no such increase, however . Results from hospital‐based studies range from no increase to up to eight‐fold higher risks . Apart from the size and setting of the studies, there are other factors that make comparisons between studies and applicability to maternity care in England difficult.…”
Section: Introductionmentioning
confidence: 99%